Cancer: Linking Powerhouses to Suicidal Bags - Martinez-Carreres, Laia; Nasrallah, Anita; Fajas, Lluis (Frontiers in Oncology, 2017)
Membrane bound organelles are integrated into cellular networks and work together for a common goal: regulating metabolism, intracellular signaling, cellular maintenance, cell fate decision, and pathogen defense. Many of these interactions are well established, but little is known about the interplay between mitochondria and lysosomes, and their deregulation in cancer. In this review, we will focus on the common signaling pathways of both organelles, as well as the processes in which they both physically interact, their changes under pathological conditions, and the impact on targeting those organelles for treating cancer.